MENYOAL SIKAPKEJAHATAN DI INDONESIA DI ERA INDUSTRI 4.0 - Supratman, Andi (LEGALITE, 2019)
In the industrial era 4.0 was a new chapter in the 21st century. This period was marked by openness and freedom in various fields of life. In the industrial era 4.0 is a century full of hope, laden with positive opportunities that can be exploited for a variety of human life, also laden with negative challenges because there has been a shift in values (social deviations) which at some level transformed into a form of crime. Crimes which is endemic in developing countries like Indonesia is certainly not the same as in developed countries. In addition, the potential for crime is caused by stretching industry 4.0. Thus, the need for special therapy / fomula to minimize the crime that will occur in the future.